Pengembangan Game Edukasi pada Materi Negara Kesatuan Republik Indonesia Kelas XI SMA - Yola Sepkia; Mutiara Felicita Amsal; Khairul Alfahani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The low level of student engagement in Pancasila and Citizenship Education (PPKn) learning indicates the need for innovative learning media that are appropriate to the characteristics of the digital generation. Learning that is still dominated by non-interactive media tends to be less able to encourage active participation and focus on student learning. This study aims to develop an adventure educational game based on the Zep Quiz digital platform on the sub-material of Threats, Challenges, Obstacles, and Disturbances (ATHG) in the material of the Unitary State of the Republic of Indonesia (NKRI) for grade XI high school students that meets the criteria of validity and practicality. The study uses a Research and Development approach with a 4D development model that includes the stages of define, design, develop, and disseminate. The research subjects consisted of 35 grade XI students of SMAN 4 Pariaman. Data were collected through validation sheets from material and media experts, as well as student practicality questionnaires using a Likert scale. The data analysis technique was carried out descriptively quantitatively by calculating the percentage of the product's validity and practicality levels. The results of the study indicate that the developed educational game has a very valid level of material and media validity, and a very practical level among students. These findings indicate that the Zep Quiz-based educational game is suitable for use as a supplementary learning medium to increase student engagement in PPKn learning in high school.